2013
DOI: 10.1038/ni.2547
|View full text |Cite
|
Sign up to set email alerts
|

Secondary T cell–T cell synaptic interactions drive the differentiation of protective CD8+ T cells

Abstract: Immunization results in the differentiation of CD8+ T cells, such that they acquire effector capabilities and convert into a memory pool capable of rapid response upon re-exposure. The initial priming of T cells takes place via an immunological synapse (IS) formed with an antigen-presenting cell (APC). By disrupting synaptic stability at different times, we show that CD8+ T cell differentiation requires cell interactions beyond those made with APC. We identify a `Critical Differentiation Period' (CDP) characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
137
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(144 citation statements)
references
References 48 publications
6
137
1
Order By: Relevance
“…It is becoming better appreciated that, during the course of their activation, T cells form substantial homo-and heterotypic clusters around the activating APC and that direct T cell-T cell signaling occurs within these clusters (52)(53)(54)(55)(56). In the context of our study, we believe that critical CD28-B7 interactions may be occurring within these T cell clusters.…”
Section: Discussionmentioning
confidence: 62%
“…It is becoming better appreciated that, during the course of their activation, T cells form substantial homo-and heterotypic clusters around the activating APC and that direct T cell-T cell signaling occurs within these clusters (52)(53)(54)(55)(56). In the context of our study, we believe that critical CD28-B7 interactions may be occurring within these T cell clusters.…”
Section: Discussionmentioning
confidence: 62%
“…Clustered T cells secrete various regulatory factors with autocrine and paracrine activity, and the close proximity of cells within the cluster facilitates intercellular communication in a regulated microenvironment. 3,40,43,44 On the other hand, large T-cell clusters may limit or even downregulate T-cell proliferation by restricting the cells' access to essential signals or nutrients, or even by creating inhibitory environmental conditions. For example, clustering was shown to limit cytotoxic T-cell effector function and differentiation by limiting the T cells' exposure to antigen during activation, upregulating inhibitory receptors (CTLA-4) and downregulating the expression of effector molecules.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Mimicry of such niches by engineering artificial lymphoid tissues or synthetic immune niches (SINs) is an emerging field, with important implications for cell-based immune therapies. 5 A major challenge for T-cell-based immunotherapies is the necessity to expand antigen-specific T cells in large quantities while maintaining their functionality.…”
Section: Introductionmentioning
confidence: 99%
“…We now show that costimulation provided through LFA-1 is more potent than costimulation through CD28, which may arise from that fact that the type and quantity of the signals induced within the T cell by these two costimulatory receptors are distinct from each other (29).…”
Section: Countering Pge 2 Inhibition With Overexpressed Icam-1mentioning
confidence: 77%
“…Not only is ICAM-1 interaction with T cell-expressed LFA-1 crucial for the homotypic T-cell aggregation that is required for T-cell communication and exchanging information (29), but the LFA-1-ICAM-1 interaction can transduce downstream costimulatory signals and drive T-cell proliferation (6,27). We have shown that the cell-surface expression of ICAM-1 by RencaHA cells is crucial for direct priming of na€ ve CL4 T cells.…”
Section: Icam-1-lfa-1 Interactions Abrogate Inhibition In Vitromentioning
confidence: 99%